1997
DOI: 10.1294/jes.8.13
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Expression of the c-ski Gene in Equine (Thoroughbred) Tissues.

Abstract: A partial cDNA fragment of equine (Thoroughbred) , obtained on day 180 of pregnancy, were analyzed by means of reverse transcriptase-mediated PCR (RT-PCR). In all the tissues examined, the expression of c-ski genes was confirmed. Northern blot analysis was carried out to assess the relative expression levels of c-ski genes in the male fetal equine tissues.In all tissues examined, two forms of the transcripts were detected at molecular sizes of 7.8 kb and 6 kb, respectively. In the cerebellum and the lung, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…As shown in Fig. 1, the c-ski gene was expressed in all the tissues examined, which was in agreement with the previous findings made in mice by Lyons et al [8] and in equine by Yamanouchi et al [13]. The ovary was one of the tissues that intensively expressed the c-ski gene.…”
Section: Expression Of C-ski Gene In the Tissuessupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Fig. 1, the c-ski gene was expressed in all the tissues examined, which was in agreement with the previous findings made in mice by Lyons et al [8] and in equine by Yamanouchi et al [13]. The ovary was one of the tissues that intensively expressed the c-ski gene.…”
Section: Expression Of C-ski Gene In the Tissuessupporting
confidence: 91%
“…Ski has been demonstrated in a variety of tissues [8,13] as in the present study and is suggested to play multiple roles in a variety of cell types [27][28][29]. For example, Ski is expressed in proliferating myoblast [6] and uterine epithelial cells [7].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The primer set used for amplification of the partial rat c‐ ski cDNA fragment consists of the forward primer, 5′‐ACC ATC TCG TGC TTC GTG GTG GGA‐3′ and the reverse primer, 5′‐CTC CTT GCC CGT GTA ATC CTG GCT‐3′, and was designed on the basis of the DNA sequences of the mouse [10] and human [11] c‐ ski gene published in the literature [12]. The predicted PCR amplified sequence was set within exon 1 of the c‐ ski gene because of its high homology with the mouse [10] and human [11] c‐ ski , and a 561 bp product was expected to be generated [12]. Fifty microliters of the reaction mixture contained 2 μl of reverse transcription reaction as above, 60 mM Tris‐HCl (pH 8.5), 15 mM (NH 4 ) 2 SO 4 , 2 mM MgCl 2 , 200 μM each of dATP, dTTP, dGTP and dCTP, 10 pmol of each primer, and 1.25 U Taq polymerase (rTaq polymerase, Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%